Work–Life Balance as a Determinant of Employee Well-Being in the Modern Work Era - Andy Hakim; Muhammad Ardiansyah (JURNAL STUDI MANAJEMEN ORGANISASI, 2026)
The modern work era, characterized by digitalization and flexible work arrangements, has intensified the interaction between work and personal life, making work–life balance a critical issue for employee well-being. Although previous studies have examined this relationship, limited research has explored work–life balance as a central determinant of employee well-being within contemporary work contexts. This study aims to examine how work–life balance shapes employee well-being in the modern work era, with particular attention to flexible work and organizational support. This study employed a qualitative research approach using a descriptive–interpretative design. Data were collected through in-depth semi-structured interviews with 18 employees who had experienced hybrid or remote work arrangements for at least six months. Participants were selected using purposive sampling. The data were analyzed using thematic analysis, supported by triangulation through observation and document analysis to enhance credibility. The findings reveal three main themes. First, 78% of participants perceived work–life balance as a key factor in maintaining psychological stability, with clear boundaries reducing stress and emotional exhaustion. Second, 83% experienced ambivalent effects of work flexibility, as increased autonomy and time efficiency (72%) were accompanied by extended working hours and work intrusion (67%). Third, organizational support and empathetic leadership were identified as decisive determinants of balance, with 89% of participants emphasizing the importance of clear policies, realistic workloads, and supportive leadership for sustaining well-being. The findings support boundary theory, conservation of resources theory, and the job demands–resources model, demonstrating that work–life balance functions as a psychological resource that protects employee well-being when supported by effective boundary management and organizational support. Flexible work arrangements act as a double-edged sword, enhancing well-being only when embedded within supportive leadership and organizational structures.